RITUS KEMATIAN MASYARAKAT JAWA KUNA, BALI KUNA, DAN BALI SEKARANG - Rita Istari (Balai Arkeologi Yogyakarta, 2008)
Indonesia has various tribes that spread over a large number of islands, and each has their own custom or tradition which is unique and different from each other. One of the customs or traditions is the funeral ceremony which can be found among Javanese and Balinese people, that is a ceremony held when someone is passed away. Based from the old inscriptions and manuscript funeral ceremony has already rooted in the past. They have their own terminology about the ceremony, although the ceremony itself principally has the same purposes. Compared to similar ceremony still undergoes until the present time, it is assumed that the custom or tradition is inherited for generations.